Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Effect of water regime and harvest stage on essential oil accumulation in basil plant growing in sandy soil - João V. R. S. Souza; Lin Chau Ming; Marcos A. L. Santos; James E. Simon; Hector R. Juliani; João C. C. Saad (Irrigation Science, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Tracing the origins of recent Queensland fruit fly incursions into South Australia, Tasmania and New Zealand - Ángel-David Popa-Báez; Siu Fai Lee; Heng Lin Yeap; Guy Westmore; Peter Crisp; Dongmei Li; Renee Catullo; Emilie C. Cameron; Owain R. Edwards; Phillip W. Taylor; John G. Oakeshott (Biological Invasions, 2021)

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

Atrial fibrillation rhythm is associated with marked changes in metabolic and myofibrillar protein expression in left atrial appendage - Julie H. Rennison; Ling Li; Cheryl R. Lin; Beth S. Lovano; Laurie Castel; Sojin Youn Wass; Catherine C. Cantlay; Meghan McHale; A. Marc Gillinov; Reena Mehra; Belinda B. Willard; Jonathan D. Smith; et al. (Pflügers Archiv - European Journal of Physiology, 2021)

Characterization and validation of QTLs for adult plant stripe rust resistance in Chinese wheat landrace Dabaimai - M. Y. Wang; M. R. Xu; F. T. Wang; S. J. A. Shah; J. Feng; R. M. Lin; S. C. Xu (Cereal Research Communications, 2021)

The stratigraphic significance of early Cambrian (Series 2, Stage 4) trilobites from the Smith Bay Shale near Freestone Creek, Kangaroo Island - J. B. Jago; C. J. Bentley; J. R. Paterson; J. D. Holmes; T. R. Lin; X. W. Sun (Australian Journal of Earth Sciences, 2021)